2009
DOI: 10.1007/s11119-009-9147-8
|View full text |Cite
|
Sign up to set email alerts
|

Leaf nitrogen estimation in potato based on spectral data and on simulated bands of the VENμS satellite

Abstract: Relationships between leaf spectral reflectance at 400-900 nm and nitrogen levels in potato petioles and leaves were studied. Five nitrogen (N) fertilizer treatments were applied to build up levels of nitrogen variation in potato fields in Israel in spring 2006 and 2007. Reflectance of leaves was measured in the field over a spectral range of 400-900 nm. The leaves were sampled and analyzed for petiole NO 3 -N and leaf percentage N (leaf-%N). Prediction models of leaf nitrogen content were developed based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Therefore, the soluble total sugar content can be increased by reducing the content of available nitrogen, ammonium nitrogen, and available phosphorus in soil. The researchers reported that the PLSR method was stronger correlation than transformed chlorophyll absorption reflectance index (TCARI) method with leaf-%N [45]. In this study, the determination coefficient (R 2 ) was ranged from 0.316 to 0.576.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, the soluble total sugar content can be increased by reducing the content of available nitrogen, ammonium nitrogen, and available phosphorus in soil. The researchers reported that the PLSR method was stronger correlation than transformed chlorophyll absorption reflectance index (TCARI) method with leaf-%N [45]. In this study, the determination coefficient (R 2 ) was ranged from 0.316 to 0.576.…”
Section: Discussionmentioning
confidence: 83%
“…Shanahan et al (2008) indicated that a chlorophyll‐based index, the transformed soil‐adjusted vegetation index, or TSAVI, detected fewer variations in greenness or canopy vigor of cereal crops during early‐stage growth. Moreover, Cohen et al (2010) reported that the TCARI was highly correlated with leaf N concentration of a potato crop only at tuber bulking stage, but not at early growth stage. In contrast, combinations of indices using chlorophyll wavelengths, such as the MCARI/SAVIL1, performed better (| r | = 0.77) in predicting NNI values than did the widely used NDVI ( r = 0.61).…”
Section: Resultsmentioning
confidence: 99%
“…VIP values show the importance of each wavelength to the model (Cohen et al, 2010). This method was applied for the two-class PLS-DA classification model as presented by Wold et al (1993).…”
Section: Resultsmentioning
confidence: 99%